2002
DOI: 10.1258/0956462021925117
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adherence to antiretroviral medication in HIV-infected patients

Abstract: The aim of the study was to assess adherence with antiretroviral medication in a sample of HIV patients in Hong Kong and identify predictors of adherence. The study used a cross-sectional correlational design. Adherence behaviour was assessed with the use of self-reports. Other scales assessed knowledge with HIV medication, coping, health locus of control, anxiety, depression and fatigue. A blood sample was also obtained to assess CD4+ counts and viral load. Sociodemographic characteristics and medical informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
2
8

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 30 publications
10
103
2
8
Order By: Relevance
“…In our own previous work investigating these cognitive components, we found that adherence self-efficacy predicted adherence behavior over and above any other cognitive processes (Parsons, Rosof, & Mustanski, 2007). Similarly studies have found patients who believe they are able to take their medications (have high adherence self-efficacy) are more likely to be adherent (Ammassari et al, 2002;Ickovics et al, 2002;Molassiotis et al, 2002). Those who believe in the effectiveness of their HAART medication are more likely to adhere (Wagner et al, 2002); whereas nonadherent patients tend to perceive fewer benefits of HAART (Deschamps et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
“…In our own previous work investigating these cognitive components, we found that adherence self-efficacy predicted adherence behavior over and above any other cognitive processes (Parsons, Rosof, & Mustanski, 2007). Similarly studies have found patients who believe they are able to take their medications (have high adherence self-efficacy) are more likely to be adherent (Ammassari et al, 2002;Ickovics et al, 2002;Molassiotis et al, 2002). Those who believe in the effectiveness of their HAART medication are more likely to adhere (Wagner et al, 2002); whereas nonadherent patients tend to perceive fewer benefits of HAART (Deschamps et al, 2004).…”
Section: Introductionmentioning
confidence: 52%
“…Our findings on differences in internalization thus are in line with other studies showing that patients with an internal locus of control achieved better adherence than those with an external locus of control. 33 Regarding the capacity to integrate medication in daily life, adherent caregivers developed an array of solutions to practical problems and stigma. Lessadherent caregivers still perceived these problems as a daily burden.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, older age and its association with better adherence have been documented in recent literature (Barclay et al, 2007;Hinkin et al, 2002;Hinkin et al, 2004;Solomon & Halkitis, 2008 Participants who had excellent adherence also showed high level of self-efficacy regarding adherence to medication. It is conceivable that patients who believed that they could follow the medication regimen would report excellent adherence rate (Barclay et al, 2007;Molassiotis et al, 2002;Wolf et al, 2007). Result suggests that interventions should not just focus on practicing adherence behaviors, it is also important to increase their belief in their ability to follow the medication regimens (Battaglioli-DeNero, 2007;Chesney et al, 2000).…”
Section: Factors Associated With Adherencementioning
confidence: 99%